Pengaruh Authentic Leadership, Information Management, Organizational Identification dan Knowledge Management terhadap Job Performance pada PT. Hino di Jakarta Timur dan Jawa Timur - Putra, Dimas Baskoro; Emilisa, Netania; Baliartati, Beta Oki (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research aims to analyze the influence of Authentic Leadership, Information Management, Organizational Identification and Knowledge Management on Job Performance at PT. HINO in East Jakarta and East Java. Data was collected from 178 PT respondents. HINO in East Jakarta and East Java with the data collection technique used is sample. Data analysis used descriptive statistics by finding the average using SPSS version 26, as well as multiple regression analysis for hypothesis testing using SPSS version 26. Previously the instrument had been tested using validity and reliability tests in which all statement items were valid and reliable. The research results show that Authentic Leadership has a positive effect on Job performance, Information Management has a positive effect on Job Performance, Organizational Identification has a positive effect on Job performance, and Knowledge Management has a positive effect on Job performance. The managerial implication of this research is that managers make employees feel comfortable at work and provide advice to employees about their work (Authentic Leadership). And managers can help new employees adapt to new jobs for new employees by sharing information and experiences with old employees so that new employees at PT. Hino feel helped in their work (Information Management) and can also be more helpful to employees. feel ownership of the company (Organizational Identification). Apart from that, managers must help employees to gain more knowledge about old and new jobs and the company's competitors in the market (Knowledge Management). Lastly, managers must help get new information about work and employees believe that by always getting new information about their work they can maintain employee work performance so they don't miss out on new information (Job performance). Keywords: Authentic Leadership, Information Management, Organizational Identification, Knowledge Management, Job Performance.